The impact of cinematic media on the learning process: raising students’ awareness of music industry professions through musical films - de Fretes, Daniel; Elviani, Elviani; Swara, Lintang Pramudia; Dhani, Kurnia Rahmad (International Journal of Visual and Performing Arts, 2024)
Music criticism serves as a cornerstone of higher education music programs. Its discourse is indispensable for maintaining a stable music ecosystem, especially within journalistic and curatorial contexts. The Music Department at the Indonesian Institute of the Arts Yogyakarta, a research-oriented institution, has integrated a music criticism course into its core curriculum. Moreover, this course is an elective and accessible to students from diverse disciplines and institutions participating in the Kampus Merdeka program. An innovative pedagogical approach is imperative to ensure the relevance of music criticism to society and academia. This research explores film's potential as an alternative tool and approach for music criticism education. Film can enhance student engagement and learning experiences by combining auditory and visual elements. The research investigates the narrative structure of musical films and explores how these films can cultivate critical thinking among students. This study delves into dramatic structure and musicological perspectives using a qualitative descriptive methodology. This research involves the stages of film observation and focus group discussions with students in the classroom to determine which films are representative and can be used as study materials. The analysis involves Vogler's classification theory and Vladimir Propp's narrative structure. The data conclusions triangulate the analysis results using theory and data interpretation based on observations as well as focus group discussions. Findings reveal that supporting characters, often overlooked in cinematic narratives, play a significant role in mapping the music profession. This study underscores the pivotal roles of journalists and critics, demonstrating their tangible contributions to the social and cultural landscape. The study will offer a new approach to innovative music criticism education by incorporating the appreciation of musical films as a medium to enhance the ability to analyze phenomena within the arts.